A review of non-technical issues in global software development. (21st March 2011) - Mishra, Deepti; Mishra, Alok
Owing to globalisation and Information and Communication Technologies (ICT) proliferation, Global Software Development (GSD) is increasingly omnipresent. Many organisations have turned to it in the quest for higher quality software delivered on time economically. GSD is facing a variety of challenges, including non-technical challenges such as cross-cultural management, communication, collaboration, coordination, distance and time, team dynamics, trust, etc. In this paper these significant non-technical issues are reviewed. It is found that non-technical areas such as team dynamics and cross-cultural risk management have received scant attention and need further studies. Implications drawn from the review will provide knowledge to facilitate further empirical studies in these areas.